Treatment of recurrent Langerhans cell histiocytosis in children with 2-chlorodeoxyadenosine - Mottl, Hubert; Starý, Jan; Chánová, Markéta; Nekolná, Michaela; Drahokoupilová, Eva; Smelhaus, Vratislav (Leukemia & lymphoma, 2006)
The objective of this study was to evaluate the efficacy of 2-chlorodeoxyadenosine (2-CdA), a purine nucleoside analog, in treating recurrent Langerhans cell histiocytosis (LCH) in children. This study retrospectively analysed the clinical records of 13 patients who were seen in the department for recurrent LCH. These patients were treated consecutively with 2-CdA chemotherapy between July 1997 and May 2005. Median age at diagnosis was 4 years 7 months and median pre-treatment duration of disease was 16.4 months. Four children received 0.1 mg kg-1 per day for 7 days and nine patients 5 mg m-2 per day for 5 days, repeated every 21 days. The maximum number of courses of 2-CdA per patient was limited to six. Seventy-six courses of 2-CdA were administered without difficulty. All 13 patients (100%) had a clinical response documented by radiographic investigation. Nine patients did not require additional therapy and remain in complete remission (CR). Four remaining children are currently disease-free after receiving other therapy as irradiation (two cases) or maintenance chemotherapy (vinblastine, prednisone and 6-mercaptopurine) (one case) or chemotherapy (vinblastine) + irradiation (one child) ( Table I). Hematologic toxicity was minimal and no infectious complications were documented. Median follow-up after initiation of 2-CdA treatment was 4 years 3 months (range 7 months - 8 years 2 months). This experience confirms the reported efficacy of 2-CdA in the treatment of LCH. However, further studies are needed to determine the role of this agent in high-risk patient who did not achieve complete remission after 2-CdA administration.
Keywords: Immunosuppressive Agents; Adolescent; histiocytóza z Langerhansových buněk; Retrospective Studies; Infant; kojenec; retrospektivní studie; Humans; Child, Preschool; Cladribine; lokální recidiva nádoru; lidé; indukce remise; kladribin; Neoplasm Recurrence, Local; Remission Induction; Treatment Outcome; Disease-Free Survival; Child; imunosupresiva; předškolní dítě; dítě; Histiocytosis, Langerhans-Cell; přežití bez známek nemoci; mladiství; výsledek terapie